Systemic inflammation and brachial artery endothelial function in the Multi-Ethnic Study of Atherosclerosis (MESA). Issue 11 (8th April 2014) - Weiner, Shepard D; Ahmed, Hanna N; Jin, Zhezhen; Cushman, Mary; Herrington, David M; Nelson, Jennifer Clark; Di Tullio, Marco R; Homma, Shunichi
Abstract : Background and objective: Inflammation and endothelial dysfunction have been implicated in the pathogenesis of atherosclerotic vascular disease. Brachial artery flow-mediated dilation (FMD) is a reliable, non-invasive method of assessing endothelial function. We hypothesised that increased levels of systemic inflammatory markers are associated with impaired endothelial function as assessed by FMD in a multi-ethnic cohort. Methods: We assessed brachial artery FMD in 3501 participants (1739 men, 1762 women; median age 61 years) in the Multi-Ethnic Study of Atherosclerosis and measured serum concentrations of interleukin (IL)-6, C reactive protein (CRP) and tumour necrosis factor (TNF)-α receptor 1. Spearman correlation coefficients were used to evaluate the association of each inflammatory marker with FMD, adjusting for the effect of other variables associated with FMD. Results: There was a significant inverse correlation between IL-6 levels and FMD (−0.042; p=0.02) after adjustment for age, gender, race/ethnicity, education, income, low-density lipoprotein, diabetes, glucose, hypertension status and treatment, waist circumference, triglycerides, baseline brachial diameter, recent infection and use of medications that may alter inflammation. There was no significant correlation between CRP and FMD (0.008; p=0.64) or TNF-α receptor 1 and FMD (0.014; p=0.57). There was no evidence of effect modification by race/ethnicity. Conclusions: In this multi-ethnic cohort, increased levels of the pro-inflammatory cytokine IL-6 were associated with impaired endothelial function assessed by FMD. Elevated IL-6 levels may reflect a state that promotes vascular inflammation and development of subclinical atherosclerosis independent of traditional cardiovascular risk factors.